Socio-Technical Changes for Sustainable Rice Production: Rice Husk Amendment, Conservation Irrigation, and System Changes - Runkle, Benjamin R. K.; Seyfferth, Angelia L.; Reid, Matthew C.; Limmer, Matthew A.; Moreno-García, Beatriz; Reavis, Colby W.; Peña, Jasquelin; Reba, Michele L.; Adviento-Borbe, M. Arlene A.; Pinson, Shannon R. M.; Isbell, Chris (Frontiers in Agronomy, 2021)
Rice is a staple food and primary source of calories for much of the world. However, rice can be a dietary source of toxic metal(loid)s to humans, and its cultivation creates atmospheric greenhouse gas emissions and requires high water use. Because rice production consumes a significant amount of natural resources and is a large part of the global agricultural economy, increasing its sustainability could have substantial societal benefits. There are opportunities for more sustainable field production through a combination of silicon (Si) management and conservation irrigation practices. As a Si-rich soil amendment, rice husks can limit arsenic and cadmium uptake, while also providing plant vigor in drier soil conditions. Thus, husk addition and conservation irrigation may be more effective to attenuate the accumulation of toxic metal(loid)s, manage water usage and lower climate impacts when implemented together than when either is implemented separately. This modified field production system would take advantage of rice husks, which are an underutilized by-product of milled rice that is widely available near rice farm sites, and have ~10% Si content. Husk application could, alongside alternate wetting and drying or furrow irrigation management, help resolve multiple sustainability challenges in rice production: (1) limit arsenic and cadmium accumulation in rice; (2) minimize greenhouse gas emissions from rice production; (3) decrease irrigation water use; (4) improve nutrient use efficiency; (5) utilize a waste product of rice processing; and (6) maintain plant-accessible soil Si levels. This review presents the scientific basis for a shift in rice production practices and considers complementary rice breeding efforts. It then examines socio-technical considerations for how such a shift in production practices could be implemented by farmers and millers together and may bring rice production closer to a bio-circular economy. This paper's purpose is to advocate for a changed rice production method for consideration by community stakeholders, including producers, millers, breeders, extension specialists, supply chain organizations, and consumers, while highlighting remaining research and implementation questions.